Studying nanotoxic effects of CdTe quantum dots in Trypanosoma cruzi - Vieira, Cecilia Stahl (2011)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Transmissores de Leishmanioses. Setor de Entomologia Médica e Forense. Rio de Janeiro, RJ, Brasil.